MATHEMATICAL MODELING OF DYNAMICS BRAKING BIAXIAL TROLLEYBUS - K. I. Mazanik (Системный анализ и прикладная информатика)
The article describes the questions of braking of trolleybus by working braking system with connected and disconnected electric drive motor. Main constructive differences of trolleybuses are shown including characteristics of electric drive motor in the mode of braking. Methods of road test are given. Comparison of the theoretical and experimental  research has analyzed.